EDITORIAL, FOREWORD - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
DRIVER–CAR INTERACTION & SAFETY 2016 June 16th – 17th 2016 In spring 2016, the 5th year of the conference series Driver – Car Interaction & Safety (formerly DCII – Driver-Car Interaction & Interfaces) took place again in Prague city center, in the historical building of Faculty of Transpiration Sciences, Czech Technical University in Prague. The conference DCIS, in 2014 organized in our detached faculty facility in Decin,  loosely picks up the threads of successful conference DCII2010 which was co-organized by Faculty of Transportation Sciences of Czech Technical University in Prague a few years ago and previous volumes of the conference (DCII2008, DCII2009 and DCII2010). The main mission of this conference is to continue on the discussion on the theme of interaction between Human-Machine-Infrastructure and factors influencing the road traffic safety and all the problems connected with these topics. It covered subjects which are partially sub/problems of the Human Machine Interaction and behavior influenced by road traffic, as well results from very distant disciplines. DCIS gathers under one roof the results of the research in many scientific and industrial branches, which are based on safety, transportation, industrial design, medicine or psychology. The part called “safety” gathers in additional approaches of forensic experts and road safety inspectors.  The conference was opened to participants coming from areas of basic and/or applied research, forensic experts’ departments, car industries, design and ergonomics, medical research etc. With the half-ten jubilee, this event was composed hand in hand with the original exhibition devoted to 100 years of development of Czech car bodywork focused on cabriolet and coupé style cars. Because of that, besides the standard scientific presentation which papers are included in this issue of AP CTU Proceedings, a portion of historical papers were also presented within a special session giving the attendees an interesting look into the history illustrated with real exhibits on display in a historical court of our faculty building. This issue contains a selection of scientific papers based on presentations talks and posters on display by the occasion of the 5th volume of DCIS, which successfully passed a rigorous review process. The exhibition itself is documented with printed commented catalogue in both the Czech and English languages. doc. Ing. Petr Bouchner, Ph.D. chief organizer   Scientific and Organizing Committee:  doc. Ing. Stanislav Novotný, Ph.D. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ)  doc. Ing. Machan Jaroslav, CSc. (Škoda Auto, a.s.)  prof. Ing. Votruba Zdeněk, CSc. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ)  prof. Ing. Novák Mirko, DrSc. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ)  prof. Ing. Václav Matoušek, CSc. (University of West Bohemia, Pilsen, CZ)  prof. Drs. Dr. L.J.M. Rothkrantz (Delft University of Technology, NL)  prof. Ing. Alicia Kalašová, CSc. (University of Žilina, SK)  doc. Ing. Pavel Hrubeš, Ph.D. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ)  doc. Ing. Zuzana Radová, Ph.D. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ)  Head of Scientific Committee: doc. Ing. Petr Bouchner, Ph.D. (Faculty of Transportation Sciences, Czech Tech. Univ. in Prague, CZ) Local organizing committee:  doc. Ing. Petr Bouchner, Ph.D.  doc. Ing. Stanislav Novotný, Ph.D.  Ing. Jiří First  Ing. Josef Mík, Ph.D.  Ing. Petra Skolilová  Head of organization committee: Ing. Alina Mashko Guarantor of the peer review process: Petr Bouchner  Guarantor of language editing: Jan Feit  Guest Editor: Alina Mashko